Performance Analysis of Concurrent Transmission with Reducing Handshakes in Multihop Wireless Mesh Networks (WMNs) - Gannapathy, Vigneswara Rao; Ahmad, Mohd Riduan; Suaidi, Mohd Kadim; Johal, Mohamad Syahrir (2009)
The IEEE 802.11 Distributed Coordination Function (DCF) Medium Access Control(MAC) protocol continues to suffer from throughput degradation when directly applied in multi-hop Wireless Mesh Network (WMN). The Request-to-Send/Clear-to-Send (RTS/CTS) signaling partially solved hidden node problems however the exposed node problems remain unaddressed. These exposed nodes lead to throughput degradation especially when the transmission in multi-hop networks is considered. The major reason for this poor performance is the restricted nature of the IEEE 802.11 MAC, which does not allow exposed nodes to initiates its transmission for the entire duration of ongoing transmission. Moreover,since multi-hop communication such as wireless mesh network transfer the data packet via intermediate nodes, the amount of control handshakes that take place at each intermediate node significantly reduce the throughput. This project proposes a set of enhancement to the existing IEEE 802.11 DCF MAC by enabling concurrent transmission by the exposed nodes and reduces the amount of handshakes required at every hop until the data packet reaches its destination. Analytical models are developed for analytical study of MAC protocols operating in multi-hop mesh networks and simulated over quasi-static Rayleigh fading channel. The multi-hop network performances are evaluated in terms of throughput and delay. The protocol outperforms the existing IEEE DCF MAC with more than 260% increase in overall throughput of multi-hop WMN.